UPAYA GURU DALAM MENINGKATKAN KEMAMPUAN SISWA MEMBACA ALQUR'AN DAN HADIS SESUAI DENGAN ILMU TAJWID DI MTSN 06 PILADANG LIMA PULUH KOTA - Sari Dewi; Bambang Isnando; Yetniati (CV. ADIBA AISHA AMIRA, 2024)
The aims of this research are: 1) Adding insight to people who read it, 2) As a contribution to stakeholders, 3) Improving students' reading in reading the Qur'an and Hadith properly and correctly. This research uses the Participant action research method, The researcher went directly to the field, through observations and interviews with related teachers. From the research in the field there were several things that became the source of the reasons for the research, including: MTs students, namely: students who are growing and looking for their identity and need attention from teachers when doing mistakes, including in reading the Al- Qur'an and Hadith, even though students have learned to read and study the Al-Qur'an and Hadith, there are still many who do not understand how to read the Al-Qur'an and Hadith properly and correctly, there are still many children who cannot yet practice it, both in terms of makhraj and the properties of the letters, therefore it is necessary for teachers to make efforts to improve students' ability to read the Qur'an and Hadith according to Tajweed Science.